Italian pool of asbestos workers cohorts: mortality trends of asbestos-related neoplasms after long time since first exposure. Issue 12 (3rd August 2017) - Ferrante, Daniela; Chellini, Elisabetta; Merler, Enzo; Pavone, Venere; Silvestri, Stefano; Miligi, Lucia; Gorini, Giuseppe; Bressan, Vittoria; Girardi, Paolo; Ancona, Laura; Romeo, Elisa; Luberto, Ferdinando; et al.
Abstract : Objective: Asbestos is a known human carcinogen, with evidence for malignant mesothelioma (MM), cancers of lung, ovary, larynx and possibly other organs. MM rates are predicted to increase with a power of time since first exposure (TSFE), but the possible long-term attenuation of the trend is debated. The asbestos ban enforced in Italy in 1992 gives an opportunity to measure long-term cancer risk in formerly exposed workers. Methods: Pool of 43 previously studied Italian asbestos cohorts (asbestos cement, rolling stock, shipbuilding), with mortality follow-up updated to 2010. SMRs were computed for the 1970â€"2010 period, for the major causes, with consideration of duration and TSFE, using reference rates by age, sex, region and calendar period. Results: The study included 51 801 subjects (5741 women): 55.9% alive, 42.6% died (cause known for 95%) and 1.5% lost to follow-up. Mortality was significantly increased for all deaths (SMR: men: 1.05, 95% CI 1.03 to 1.06; women: 1.17, 95% CI to 1.12 to 1.22), all malignancies combined (SMR: men: 1.17, 95% CI to 1.14 to 1.20; women: 1.33, 95% CI 1.24 to 1.43), pleural and peritoneal malignancies (SMR: men: 13.28 and 4.77, 95% CI 12.24 to 14.37 and 4.00 to 5.64; women: 28.44 and 6.75, 95% CI 23.83 to 33.69 and 4.70 to 9.39), lung (SMR: men: 1.26, 95% CI 1.21 to 1.31; women: 1.43, 95% CI 1.13 to 1.78) and ovarian cancer (SMR=1.38, 95% CI 1.00 to 1.87) and asbestosis (SMR: men: 300.7, 95% CI 270.7 to 333.2; women: 389.6, 95% CI 290.1 to 512.3). Pleural cancer rate increased during the first 40 years of TSFE and reached a plateau after. Discussion: The study confirmed the increased risk for cancer of the lung, ovary, pleura and peritoneum but not of the larynx and the digestive tract. Pleural cancer mortality reached a plateau at long TSFE, coherently with recent reports.